2017
DOI: 10.1002/qre.2218
|View full text |Cite
|
Sign up to set email alerts
|

The effects of violations of the multivariate normality assumption in multivariate Shewhart and MEWMA control charts

Abstract: A multivariate Shewhart and a multivariate exponentially weighted moving average control charts are types of multivariate control charts for monitoring the mean vector. For those control charts, a multivariate normal distribution is an important assumption that is used to describe a behavior of a set of quality characteristics of interest. This research explores the sensitivity of average run lengths and standard deviation of run lengths for the multivariate Shewhart and the multivariate exponentially weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Whereas, the chi‐square limit in equation () is only appropriate when the covariance is known. Nidsunkid et al 10 suggested that the samples size must be chosen at least 250 (m250) when k is large (k10) to approximated the correct UCL.…”
Section: Hotelling's T2 Control Chartmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, the chi‐square limit in equation () is only appropriate when the covariance is known. Nidsunkid et al 10 suggested that the samples size must be chosen at least 250 (m250) when k is large (k10) to approximated the correct UCL.…”
Section: Hotelling's T2 Control Chartmentioning
confidence: 99%
“…Meanwhile, Nidsunkid et al 9 presented the performance of multivariate control charts such as MCUSUM control charts when the multivariate normal distribution assumption is incorrect. Previously, Nidsunkid et al 10 studied the performance of multivariate Shewhart and MEWMA control charts when the random vector comes from multivariate normal and multivariate non‐normal distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic assumption for multivariate control charts is multivariate normality, which is completely specified by its expected value µ and covariance matrix Σ. In general, this assumption many times cannot be supported by real data (Nidsunkid Borkowski, & Budsaba, 2017). This study will consider the underlying distribution of the observation is the multivariate t distribution.…”
Section: Deming's Four Principle: the Knowledge Of Variationmentioning
confidence: 99%
“…Nidsunkid et al (2017) explora a sensibilidade dos comprimentos médios de execução para o gráfico multivariado de Shewhart e para gráficos MEWMA em casos que a suposição de normalidade está incorreta Zhang et al (2014). utilizam dois gráficos de controle multivariados do tipo Shewhart para monitorar o termo de tendência linear e a correlação dentro do perfil separadamente na fase II.…”
unclassified